Investigation of accuracy in microdrilling with minimum quantity lubrication - Mohammad, Yeakub Ali; Farhana, Sulaiman; Banu, Asfana; Mohamed, Abd. Rahman; Al Hazza, Muataz Hazza Faizi (Trans Tech Publications Ltd, 2017)
Cutting fluid plays an important role in machining processes to achieve dimensional accuracy, reduce tool wear, and improve tool life. Use of flood cooling conventionally used in machining is not cost effective and consumption of huge amount of cutting fluids is not health and environmental friendly. Therefore, one of the alternatives is to use minimum quantity of lubrication (MQL) in machining process. MQL is eco-friendly and has economical advantage on manufacturing cost. Study of the effects of MQL on burrs and aspect ratio should be carried out because burrs and aspect ratio are important issues in microdrilled parts used as microfluidic channels in bio-medical applications. In case of micromachining, flood cooling is not recommended to avoid any possible damage of the microstructures. As a result alternative solutions are sought. This paper investigates and compares burrs and aspect ratio in dry microdrilling and microdrilling with the presence of MQL on aluminium alloy 1100. The relationship among tool diameter, feed rate, and spindle speed on the area affected by burrs and drilled hole aspect ratio are analysed. The values of aspect ratio for both conditions show that there is slight improvement on aspect ratio in MQL over dry drilling. MQL has significant influence on affected area by burrs. It is observed that low spindle speed, high feed rate, and bigger drill diameter should be used along with MQL to reduce burrs.